Economics of Institutions and Law - PETRETTO, ALESSANDRO (Manuali - Scienze Sociali, 2017)
This book provides a set of lectures for an intermediate course in Public economics devoted to four topics, in many elements related each other. The first one is the Economics of institutions and political economy, as a general framework to analyze the public intervention in modern economies. The second one is the Economics of Law, which is at the basis of the working of the exchange economy. The third one is the Economics of public services enterprises ownership and the fourth one is the Economics of the organization of public administration in providing public services, with particular reference to the National health care systems and to the local public municipalities. As the standard textbooks in the field usually do not treat within unitary and comprehensive terms these issues, the book would provide an attempt in this direction.